The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/su10040980
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Complex Societal Problems: Enabling Multiple Dimensions of Proximity to Sustain Partnerships for Collective Impact in Quebec

Abstract: Sustainable solutions for complex societal problems, like poverty, require informing stakeholders about progress and changes needed as they collaborate. Yet, inter-organizational collaboration researchers highlight monumental challenges in measuring seemingly intangible factors during collective impact processes. We grapple with the question: How can decision-makers coherently conceptualize and measure seemingly intangible factors to sustain partnerships for the emergence of collective impact? We conducted an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…Others showed that the role of geographical distance between research subjects in scientific cooperation networks has not weakened but has instead strengthened [42,43]. In conclusion, the relative importance of proximity of different dimensions in the process of scientific cooperation changes depending on the type of knowledge produced [44,45]. It is worth emphasizing that there is a large gap in the resources of higher education between Chinese cities, which is an important factor affecting the scientific cooperation of Chinese scientists.…”
Section: Literature Review and Hypothesesmentioning
confidence: 94%
“…Others showed that the role of geographical distance between research subjects in scientific cooperation networks has not weakened but has instead strengthened [42,43]. In conclusion, the relative importance of proximity of different dimensions in the process of scientific cooperation changes depending on the type of knowledge produced [44,45]. It is worth emphasizing that there is a large gap in the resources of higher education between Chinese cities, which is an important factor affecting the scientific cooperation of Chinese scientists.…”
Section: Literature Review and Hypothesesmentioning
confidence: 94%
“…The relational dimension of social capital that impacts inter-organizational learning is trust. Scholars highlight that trust "facilitates the openness for exchange of tacit knowledge, which is relatively difficult to communicate or trade in markets, and durability of relationships, which otherwise may collapse when problems arise between exchanging partners in pure market relationships" [183]. The literature highlights that the stronger the trust between partners, the stronger their ties and the more they can learn and innovate in a partnership [122,183,184].…”
Section: Relational Dimension Of Social Capital: Trustmentioning
confidence: 99%
“…Scholars define cognitive distance as differences of partner organizations with regards to their organizational frames, which are "interpretations used to make sense of the world." In other words, cognitive distance is to do with the "similarity in actors' frames of reference, and mental modes facilitate effective and efficient communication and transfer of knowledge, although some extent of differentiation is needed for new ideas, creativity, and innovation to emerge" [183]. On the other hand, institutional distance is referred to as field-level differences between organizations with regards to their institutional logics which are "taken-for-granted assumptions and practices that shape the behavior of organizations in specific societal sectors" [189].…”
Section: Cognitive Dimension Of Social Capital: Optimal Distancementioning
confidence: 99%
“…By virtue of its mandate, this convener needs to have an extensive network of ties to different actors across society. Beyond the existence of ties, the convening entity should be one that can draw attention to the problem and exhort action from actors tied to its causes or solutions in relation to their core resources and capabilities [44,63,64]. Finally, the convener also needs to have a reputation and credibility that can accord legitimacy to the initiative [20,44], bring more actors into the fold, and ensure all actors are informed and engaged [63].…”
Section: Modularizing Societal Problemsmentioning
confidence: 99%
“…Government organizations have been a natural choice to play this convening role since both economic growth and societal well-being fall within their mandate, and they have considerable authority over other societal actors [39,63]. They can employ a variety of tools ranging from persuasion and incentives to strictly enforced regulations to shape the behavior of others.…”
Section: Modularizing Societal Problemsmentioning
confidence: 99%